Você sabe de onde eu venho? um estudo da transição escolar de alunos do campo para a cidade - OLIVEIRA, Keyla Sorene Rodrigues de (2020)
This work is linked to the Research Line: Educational Institutions, Curriculum, Formative and Teaching Work and to the Research Group: Education and Social Representations, parts of the Graduate Program in Education at the Federal University of Maranhão. Education as a right for all does not occur in a homogeneous way, presenting itself as diverse as the Brazilian social contexts. In this work we present a universe of subjects from the countryside who, without leaving their place of origin, start attending urban schools, and begin to have contact with the new reality that is unveiled, through commuting. In order to study psychosocial aspects present in the school transition experienced by students residing in the rural area of the municipality of São João dos Patos, in the state of Maranhão, this study was carried out with the substance of these subjects' daily lives. Educational and pedagogical aspects concerning the theme were supported mainly by Arroyo (2004), Caldart (2004), Coutinho (2009), Freire (1996) and Saviani (2013). The Theory of Social Representations developed by Moscovici (1995; 2003; 2012) and continued by Jodelet (2001; 2005), was chosen to support this study as it seeks to understand how common sense knowledge is formed within social groups and how their practices groups are driven by these symbolic constructions. A structural approach bias to this theory was also used, following studies by Abric (2000; 2001; 2003) and Sá (1996; 1998; 2002). To this end, we selected a sample of twenty students living in rural communities in the municipality and enrolled in the sixth year of the urban school Escola Municipal Eduardo Coelho Mendes, as well as ten teachers from the school under analysis. Data were collected in a similar way for all subjects, through profile questionnaires and the Free Word Association Technique-TALP. Teachers were presented with three inductive questions to be answered with four evocations each. To the students, five inducing questions that asked for four answers each, and, in addition, discursive responses to the topics covered were recorded. Data analysis was performed by combining techniques, with Content Analysis proposed by Bardin (2010) as the starting point for analyzing all sets of responses. The data were also submitted to analyzes performed using the Iramuteq software. The results of the analyzes showed that students like to live and study in the countryside, thus distancing themselves from the way of thinking about this reality manifested by their teachers, who expressed unfavorable aspects related to the theme. They also showed that the Social Representations that students from the countryside expressed about the urban school before they met it were close to those they formed after attending it, and their expectations were met. In relation to the confrontations reported by students during the school transition, this study revealed that the representations of teachers, more linked to pedagogical aspects, distanced themselves from those expressed by the students themselves, who are most affected by the loneliness experienced in the new environment. It is hoped that this study can support pedagogical interventions in schools that experience the context studied.